Penggunaan Media Poster terhadap Peningkatan Pengetahuan Tentang Kesehatan Reproduksi pada Remaja di Kecamatan Pengkadan - Desi Asih Purwanti; Sella Ridha Agfiany (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Adolescent health, especially reproductive and sexual health, is important for achieving sustainable development. The environment in which adolescents grow up today continues to change rapidly along with the rapid growth of the technology and information sector. With increasing activity on social media platforms such as Instagram, Facebook, Twitter, and YouTube, adolescents are increasingly exposed to information that can trigger risky behavior (Steinberg, 2019). Adolescents' unpreparedness in facing these changes can lead to various negative behaviors. Reproductive health education is very important to be given to children as early as possible so that children avoid various problems and juvenile delinquency that arise due to a lack of understanding of reproductive health (Tedju, 2019). The purpose of this community service activity is to increase adolescent knowledge, especially about reproductive health. The activity was carried out in Pengkadan District, Kapuas Hulu Regency. Educational activities in the form of counseling using poster media. The counseling was attended by 30 people. In community service, the counseling method was used through poster media for adolescents, then assessed using pre-tests and post-tests to determine whether there was an increase in reproductive health knowledge. The results of Community Service showed an increase in reproductive health knowledge in adolescents after being given counseling.